Supported Pt–Cu bimetallic catalysts: preparation and synergic effects in their catalytic oxidative degradation of aniline. Issue 54 (22nd October 2021) - Ding, Qiuyue; Zhang, Wumin; Zhu, Yuanyuan; Wang, Lu; Feng, Xinyuan; Xi, Yanyan; Lin, Xufeng
Abstract : An AC supported Pt–Cu catalyst prepared with a new methanal reduction method was found to be quite effective for catalytic Fenton oxidation of aniline in water. The Pt and Cu components showed a synergic effect for the catalytic process. Abstract : Catalytic Fenton oxidation is an effective way to remove organic pollutants in water, and the performance of the catalyst is a key issue for the competiveness of this method. In this work, various supported bimetallic Pt–Cu catalysts were prepared by different impregnation methods and their performances for catalytic Fenton oxidation of aniline in water were investigated. In the different impregnation methods employed, factors including the reduction method of the metal precursor, type of catalytic support, and loading of metal were investigated. The effect of different reduction methods on actual loadings of the active components on the supported Pt–Cu catalysts showed the order of (i) H2 reduction > (ii) liquid phase methanal reduction. Meanwhile, compared with the monometallic catalysts, the Pt–Cu alloy phase (mainly in the form of PtCu3 ) was generated and the specific surface area was significantly reduced for the bimetallic catalysts. In the process of Fenton catalytic oxidation of aniline, it was found that most of the prepared catalysts had a certain catalytic activity for H2 O2 accompanied with aniline degradation. It was found that Pt0.5 Cu1.5 /AC (where AC denotes activated carbon) exhibited superb catalytic activity compared with all other prepared catalysts. In particular, aniline was almost completely mineralized in a neutral solution (500 mg L −1 aniline, 0.098 mol L −1 H2 O2 ) after 60 min at 50 °C using Pt–Cu/AC (Pt: 0.5%, Cu: 1.5%). The characterization results showed that the Pt and Cu components were rather evenly distributed on the AC support for this catalyst. More importantly, there was an obvious synergic effect on the supported bimetallic catalyst between the Pt and Cu components for the catalytic oxidation of aniline.